The deep impact of novel CoVID-19 infection in an Orthopedics and Traumatology Department: the experience of the Piacenza Hospital - Maniscalco, Pietro; Poggiali, Erika; Quattrini, Fabrizio; Ciatti, Corrado; Magnacavallo, Andrea; Caprioli, Serena; Vadacca, Giovanni; Michieletti , Emanuele; Cavanna, Luigi; Capelli, Patrizio (Acta Biomedica Atenei Parmensis, 2020)
Since February 21st, 2020 CoVID-19 spread throughout all Italy expanding like a “tsunami” from Codogno (Lodi, Lombardy, Northern Italy) to neighboring cities. In a few days Lodi, Piacenza, Milano, Brescia and Bergamo were forced to deal with this disaster starting the lockdown at different time. No national plan had been prepared. As result, CoVID-19 has paralyzed the Italian healthcare system. At time of writing, in Italy there are 169 323 infected patients and 22 260 deaths. Italy is fighting hard to manage CoVID-19 crisis even if most hospitals were unprepared to deal with massive influx of critically ill CoVID-19 patients. Piacenza in Emilia-Romagna region (Northern Italy) is one of the epicenters of the Italian pandemic, and the local hospital – Guglielmo da Saliceto – has quickly become a “CoVID-19 hospital” with the great effort of all the medical staff. Here we report the experience of our hospital, particularly the strategy adopted in the Orthopedics and Traumatology Department.